Fraturas do sistema penal : o sintoma das falsas memórias na prova testemunhal - ávila, Gustavo Noronha de (2012)
This thesis aims to evaluate the effects of false memories in relation to witnesses in the processes of criminalization and, in addition, provide preventive alternatives. Therefore, identifying ways of addressing the issue not only in the Brazilian legal system, but also in neuroscience, psychology of testimony and seeks to achieve a rapprochement with the criminal justice system more broadly, dealing with criminology. This perspective assumes the denial of the auxiliary character of criminology in relation to other criminal sciences, to reaffirm it as a key criterion in the interpretation of the whole system. From the perspective of "skidding" memory work we evaluate not only the external variables (forms of assessment and search for clues by the chief of police and the magistrate and trial by media), but also internal factors (suggestibility and induction processes, beyond possible memory changes that may lead to problems regarding the quality of information). In addition to these perspectives, we also work on the possible interpretations about the criminal justice system that can assist in alleviating the problem. In this sense, the approach of guaranteeism criminal theory proves to be quite close to what we call "harm reduction", i.e. from specific legeslative reforms, we could reduce the problem to tolerable levels. From the itinerary and the comparison between the possibilities guarantist and radical minimalist (or abolitionist), we join the last because of his scathing criticism of the system and identification of fractures of the penal system as forms of infliction of needless pain. Also for being not only a negative interpretation as well as purposeful. Finally, we conducted a field study, from a qualitative approach, where we try to identify aspects of criminalization and its influence in trying to get the story of the one who witnessed the crime. We confirm the ideas of suggestibility and induction as tonic interviews, in addition to different approaches for each case as well as the influence of media. With a comprehensive view of the criminal justice system (from the preliminary investigation to the criminal procedure itself), we realized the need for radical reduction of the system, in order to provide smaller spaces for the persistent false memories and avoid injustices beyond insufficient "harm reduction".